La falta de la prueba de ADN y la eficacia de otros medios probatorios en el juicio de impugnación de paternidad - Paullan Quishpi, Gina Paola (2025)
Paternal filiation is a crucial aspect of family law, with implications that extend beyond the legal field to encompass significant emotional, social, and economic dimensions. In Ecuador, challenging paternity is a legal figure used to question this kinship relationship, leading to complex processes that require various means of proof to establish both biological and legal truths. There are times when the defendants are absent from the sample-taking, making judicial rulingsin the paternity challenge trial difficult. To achieve our objectives, a field investigation was conducted, providing insight into the issue at hand. We employed the analytical-synthetic method, which aided in the identification and analysis of legal norms, doctrines, and jurisprudence on paternity challenges. It is evident that when a person is recognized by a non-biological father, their right to identity could be compromised. Therefore, it is imperative to strengthen the validity of evidence, including DNA, in cases of paternity challenges. Furthermore, the role of legal professionals in developing effective judicial mechanisms in these processes is crucial.